Clima organizacional y su relación con el desempeño laboral de los colaboradores en La Casa de las Enchiladas, Iquitos 2022 - Carrasco Prieto, Freysi Julissa (2023)
For this research, the objective was to determine the relationship that exists between the work environment and the work performance of the employees of the company La Casa de las Enchiladas Iquitos 2022. For the research methodology, the type of research was used descriptive, correlational and cross-sectional, with a non-experimental design. The population consisted of all the workers of the company La Casa de las Enchiladas the total sample is 80 people, the result was obtained that shows us a correlation value Pearson's equal to 0.617** which indicates a strong significant correlation according to the theory; furthermore, the sigma value (bilateral) is 0.000; according to the Decision Rule, if the value of P (significance) is less than 0.05; the alternative hypothesis is accepted. Finally, it was concluded that with a Pearson correlation value equal to 0.617** and a sigma value equal to 0.000, the alternative hypothesis is accepted and it’s affirmed that there’s a significant relationship between the organizational climate and the work performance of the workers La Casa de las Enchiladas Iquitos, 2022. The degree of strong correlation due to its level of significance, it was determined that the characteristics present in the organizational climate of the company are related to the competencies identified for the work performance of the workers.